Early Post-Cesarean Anxiety, Nausea, Vomiting, and Pain Under Spinal Anesthesia: Trajectories and Modifiable Predictors - Indah Susanti; Eza Kemal Firdaus; Septian Mirova Sebayang; Amelia Andini; Alicia Dumes Berg; Margaret Atwood; Rantiningsih Sumarni; Mesya Mesya; Asmat Burhan (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Recovery after caesarean under spinal anesthesia remains a quality gap, with scarce evidence on modifiable anesthetic practices improving recovery. Data linking the neuraxial technique, nausea, anxiety, and pain remain limited. The objective of this study was to describe postoperative nausea and vomiting, anxiety, and pain at 6, 12, and 24 hours after caesarean section under spinal anesthesia and to examine whether intrathecal adjuvant use, sensory block level, fasting duration, and American Society of Anesthesiologists (ASA) physical status were associated with these outcomes. Cross-sectional study across five hospitals; 534 women undergoing caesarean under spinal anesthesia. Exposures: intrathecal adjuvant, sensory level (≤ T6 and > T6), nil per os (NPO) time, and ASA class. Outcomes: postoperative nausea and vomiting (PONV) using Rhodes Index of Nausea, Vomiting, and Retching (RINVR), anxiety using State-Trait Anxiety-State STAI-S), pain at 6,12,24 h; generalized estimating equations Poisson and linear models. A total of 534 women completed the study (mean age, 31.8 years; mean body mass index, 29.3). Symptom burden was greatest in the early postoperative period: postoperative nausea and vomiting and pain were highest at 6 hours, whereas anxiety peaked at 12 hours. By 24 hours, symptoms had declined, although substantial proportions of women continued to report nausea and pain. Better ASA physical status (class I-II) was associated with lower RINVR and STAI-S. These findings suggest that modifiable perioperative factors may help inform strategies to improve early post-caesarean recovery and guide postoperative nursing monitoring and symptom management.